Verb Matters: Exploring Morphological and Syntactic Differences Between English and Indonesian Language System - Idaryani, Idaryani (Journal of English Language and Education, 2025)
This study aims to investigate the distinctive differences of verbs’ characteristics in English and Indonesian languages. It explored the similarities and differences in the features of verbs in the two languages by comparing characteristics of the verbs based on syntactic and morphological aspects from both languages. The study employs contrastive analysis approach. Data were collected from linguistics books and journal articles from both languages. The results reveal that, based on various analyses of the following classifications—forms, functions, meanings, and positions—there are nearly universal parallels and notable differences in the usage of verbs between the two languages. In terms of verb forms, English system exhibits multiple features of verbs without affixation whereas the Indonesian verbs vary due to the affixation attachment. English verbs syntactically are adhered by time aspects but Indonesian language verbs do not indicate time markers.  The morphological and syntactical structures of the English and Indonesian languages notably differ that English teachers should take into account when teaching English. To understand the contrastive similarities and dissimilarities between both languages contribute to crucial implications teaching instruction. Consequently, having a proper knowledge of those crucial aspects enables the teachers and Indonesian learners to solve the challenges they face in the process of learning English as a foreign language by having a thorough understanding of these important verb features between the English and Indonesian languages.